Detection of gliclazide in aqueous samples using liquid chromatography/time-of-flight/mass spectrometry - Al-Qaim, Fouad Fadhil; Md Pauzi Abdullah,; Jalifah Latip,; Wan Mohd Afiq Wan Mohd Khalik,; Nurfaizah Abu Tahrim,; Nurul Auni Zainal Abidin,; Mohamed Rozali Othman, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The big challenge for the detection of pharmaceutical residues in water samples is the type of ionization mode in terms of positive or negative ionization which plays an important role to identify and quantify the analytes using liquid chromatography/mass spectrometry. An analytical method was applied to analysis of gliclazide (diabetic drug) in surface water and wastewater from sewage treatment plants and hospitals. The proposed analytical method allows simultaneous isolation and concentration procedure using solid phase extraction (Oasis HLB) prior to separation using high-performance liquid chromatography. The detection and confirmation was achieved by applying time-of-flight analyzer. The limits of quantification were as low as 1.4 ng/L (deionized water), 4 ng/L (surface water), 27 ng/L (hospital influent), 10 ng/L (hospital effluent), 6 ng/L (sewage treatment plant effluent) and 21 ng/L (sewage treatment plant influent), respectively. On average, good recoveries of higher than 87% were obtained for gliclazide in the studied samples. The proposed method successfully determined and quantified gliclazide in surface water and wastewater. The results showed that gliclazide is a persistent compound in sewage treatment effluents as well as in the recipient rivers. Gliclazide was detected in all samples and the highest concentration was 130 ng/L in influent of sewage treatment plant.